POTENTIAL APPLICATIONS OF Lactobacillus CELL COMPONENTS IN THE BIOTECHNOLOGY OF HUMAN LYMPHOBLASTOID INTERFERON - V.V. Pits; O.P. Trokhimenko; V.Yu. Polishchuk; S.O. Soloviov; I.V. Dziublyk; I..M. Fedianovych; Z.F. Kysil; N.A. Bobyr (Biotechnologia Acta)
Aim. The study aimed to investigate the role of lactobacillus cell components and their effective use in increasing the efficiency of human lymphoblastoid interferon production.